Persistent response of furmonertinib plus anlotinib in a lung adenocarcinoma patient with an EGFR exon 20 insertion mutation: A case report - Chen, Xuesong; Zha, Wangjian; Su, Mei; Meng, Nan; Cao, Shuliang; Niu, Beifang; Qi, Xu (Frontiers in Pharmacology, 2023)
Insertions in exon 20 represent the third most common type of EGFR mutation following in-frame deletions in exon 19 and the point mutation L858R in exon 21. They are generally associated with primary resistance to EGFR-TKIs. Although mobocertinib and amivantamab were approved for adult patients with non-small cell lung cancer (NSCLC) harboring EGFR exon 20 insertion mutations, the efficacy of these two agents was rather moderate. Therefore, other more potent targeted agents are urgently needed. Here, we report a patient with advanced lung adenocarcinoma harboring an EGFR exon 20 insertion mutation (NM_005228: exon 20: c.2316_2321dup: p.773_774dup). After experiencing platinum-based chemotherapy, this patient received a combination of furmonertinib and anlotinib and achieved lasting stable disease (SD). The treatment was well tolerated, and only mild hand-foot syndrome was reported from the patient. To the best of our knowledge, this case firstly reported the encouraging efficacy of combined furmonertinib and anlotinib in an advanced lung adenocarcinoma patient with an EGFR exon 20 insertion mutation who was previously treated with platinum-based chemotherapy. In addition, we summarize the recent literature on therapies against NSCLC with EGFR exon 20 insertion mutations. This case might provide an alternative approach for clinical oncologists.